(untitled) (Journal of Asian Development Studies, 2025)
Divorce is considered a social stigma in traditional societies like Pakistan, which restrains women’s freedom, and sometimes, they are considered a burden on the family. There are different stigmas associated with divorce. They experience serious socio-economic consequences and are often isolated. This isolation led to psychological distress and depression, making these women more vulnerable. The studies on this issue are minimal, particularly in KPK, where such issues are always concealed and people avoid discussing them openly. So, this study aimed to explore the sociocultural, economic realities, and systematic discrimination that divorced women face. The geographical universe of the study was Swabi, and using the referential sampling technique, twelve in-depth interviews were conducted with divorced women from the Swabi district of KPK. Thematic analysis of the data was done. The findings revealed that early marriages, limited or no choice to choose a male partner as husband, post-marriage abuse, and absence of any social support were found to be the main issues reported by respondents. Even in the worst circumstances, divorced women struggled for economic stability, child rearing, and single parenting challenges, which also led to stress and depression. The stigma further adds a caveat to it. The study emphasizes the importance of community awareness and social support programs with a gender-sensitive policy reform. Women may be provided with free legal aid and vocational training to help them achieve economic independence.